Trade Facilitation and the Extensive and Intensive Margins of Trade - Maria Persson (Lund University, School of Economics and Management, Department of Economics, 2008)
Exploring the link between trade facilitation and the extensive and intensive margins of trade, the paper has two aims. The first and main objective is to investigate whether the extensive margin of trade in homogeneous and differentiated goods is affected in the same way by cross-border trade transaction costs. The second objective is to compare the implications for the extensive and intensive margins to ascertain the margin at which these transaction costs matter the most, again controlling for the type of goods being traded. Very detailed mirror data on imports to EU countries from developing countries in 2005 is utilized to decompose these countries' exports into its extensive and intensive margins. Using the number of days needed to export a good as a proxy for trade transaction costs, econometric evidence is found that there is a significant and negative association between export transaction costs and the extensive margin for differentiated goods: developing countries with high transaction costs will export significantly fewer differentiated goods. However, no such negative effect on the extensive margin is found for homogeneous goods. Comparing the two margins' effects, evidence is found that, for differentiated goods, the extensive margin is more negatively affected by export transaction costs than the intensive margin. Results also indicate that to the extent that there is an overall negative trade effect on homogeneous goods from export transaction costs, this negative effect stems from effects on the intensive margin.
Keywords: C21; F13; O24; 330; Trade Facilitation; Extensive and Intensive Margins of Trade; Export Diversification; Homogeneous and Differentiated Goods